Molecular Characterization of Streptococcus agalactiae Isolates from Pregnant Women in Kathmandu City - Kusum Shrestha; Anil Kumar Sah; Neetu Singh; Pramila Parajuli; Rameshwar Adhikari (Journal of Tropical Medicine)
Introduction. Group B streptococci (GBS) are globally recognized as one of the leading causes of neonatal sepsis and meningitis and is also known to cause adverse pregnancy outcomes such as stillbirths and miscarriages. Thus, detailed investigation of GBS in pregnant women has special significance in public health related researches. Objectives. The present study is aimed at evaluating the prevalence of GBS colonization among pregnant women in Kathmandu city. Methods. The study was carried out among 125 pregnant women at their trimester (35–37 weeks) (during the time period between January and June in 2018). The prevalence was determined by the culture method in HiCrome Strep B Selective Agar Base and then by using the PCR technique. The serotypes were evaluated by multiplex PCR analysis, while the antibiotics susceptibility tests were performed using the disk diffusion method. Results. Among 125 samples studied, GBS were recorded in 24 samples (implying a prevalence of 19.2%). Furthermore, using the multiplex PCR, among 24 GBS-positive samples, 13 (54.17%) were found to be typeable while 11 (45.83%) were nontypeable. The most abundant serotype recorded in this study was type III (33.33) while the serotypes IV, V, VI, VII, and VIII were not found. Conclusion. The isolates were sensitive towards some antibiotics such as linezolid and ceftriaxone 100%, whereas penicillin 50% and vancomycin 75% but were resistant to tetracycline and ertapenem. Serotype III was found to be predominant in the samples collected during the study period. The observed prevalence was significantly associated with the gestational period, whereas no relationship was found for other risk factors.